2018
DOI: 10.1108/ejmbe-11-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the formation of e-loyalty towards tourism destinations

Abstract: Purpose-The purpose of this paper is to determine the drivers of the formation of e-loyalty in a tourist destination, providing a model composed of variables that are under the control of the firm along with others that are not fully controllable by professionals. Design/methodology/approach-The study was carried out with a sample of 497 subjects, university students and online consumers, and with the use of structural equations (partial least squares). Findings-Results show that young people give a high valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
2
13
0
2
Order By: Relevance
“…Regarding responses to items, it can be confirmed that young people give importance to all the variables presented in this study, thus, confirming the "technological" nature of this population segment [23]. The results are in line with other studies in which young people value more than 50% of the items related to the design and the personalization of the website in the market orientation framework [13,83].…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding responses to items, it can be confirmed that young people give importance to all the variables presented in this study, thus, confirming the "technological" nature of this population segment [23]. The results are in line with other studies in which young people value more than 50% of the items related to the design and the personalization of the website in the market orientation framework [13,83].…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…Numerous authors have also studied website design quality and its influence both in tourism and in other sectors [4,83]. The model of website quality by DeLone and McLean [84][85][86] included system quality, information quality, and service quality.…”
Section: Hypothesis 2 (H2b)mentioning
confidence: 99%
“…Alam and Yasin [12] state that when customers are satisfied, and their expectations have been met or exceeded by the service provider, the customer's intention to repurchase is most likely to reinforced. Thus, e-satisfaction is a fundamental factor when it comes to retaining customers, and subsequently this has a direct effect on customer loyalty [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Within the third perspective ( objective perspective ), fall all the authors focusing their attention on the main objectives recognized to the online reputation, such as inducing cooperation (Bakos and Dellarocas, 2011); mitigating information asymmetry (Novotny and Spiekermann, 2017; Lin et al , 2016); influencing customers during their online purchasing (Singh et al , 2016a); reducing transaction risks (Novotny and Spiekermann, 2017); capturing clients and reaching sales goals and higher prices (Díaz and Rodríguez, 2018; Diana-Jens and Ruibal, 2015; Yoganarasimhan, 2013); influencing the firms’ value perceived by users (Parra-Lopez et al , 2018); helping community members make decisions (Dellarocas, 2010).…”
Section: Resultsmentioning
confidence: 99%